2013
DOI: 10.1080/19443994.2013.809984
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of nitrate ions onto activated carbon prepared from rice husk by NaOH activation

Abstract: A B S T R A C TPrecursor was prepared from rice husk under different carbonization temperatures. Then, activated carbon (AC) was synthesized by NaOH activation. The specific surface area of carbon increased with temperature rise up to 600˚C, but decreased rapidly over 600˚C. So, the AC obtained at 600˚C possessed the outstanding surface area of 2,802 m 2 /g. And, its adsorption activity of nitrate was carried out at initial concentration of 50-400 mg/L. The results showed that the maximum adsorption capacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Figure 4(b) shows that a -GA-10%, a -GA-14% and a -GA-18% exhibit similar adsorption capability for pb 2+ despite of their significant differences in volume. Their adsorption capability could be as high as 80 mg g −1 , which is higher than those of a -GA-22% (about 68 mg g −1 ) and GA (55 mg g −1 ) and much better than that of activated carbon383940. That means without sacrificing the adsorption capacity, the volume of a -GA-N can be controlled to save space and it is more convenient and efficient to remove some pollutants out of water.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4(b) shows that a -GA-10%, a -GA-14% and a -GA-18% exhibit similar adsorption capability for pb 2+ despite of their significant differences in volume. Their adsorption capability could be as high as 80 mg g −1 , which is higher than those of a -GA-22% (about 68 mg g −1 ) and GA (55 mg g −1 ) and much better than that of activated carbon383940. That means without sacrificing the adsorption capacity, the volume of a -GA-N can be controlled to save space and it is more convenient and efficient to remove some pollutants out of water.…”
Section: Resultsmentioning
confidence: 99%
“…Authors of the article (Zhang et al, 2014) suggested that the adsorption rate for carbon adsorbent depended on the availability of adsorption sites rather than on the ions concentration in solution, but it would have rather related to ion-exchange mechanism in double electric layer around the carbon adsorbent, and not only with the presence of the polar functional groups on its surface. Although, on the other hand, the increase in the number of ions in a double layer of carbon may be the result of the increase in the number of polar functional groups on its surface.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising, because the oxidation of carbon adsorbent with H 2 O 2 causes an increase in cation-exchange groups on the surface, but it did not result in growth of the ammonium cation sorption, but increased the sorption of anions of nitrate and nitrite. By comparing the values of sorption capacity, designated in dynamic analysis (SPE) and the values of the adsorption of nitrate ion in static conditions, as it was obtained by the authors of the work (Zhang et al, 2014), it turned out that our values are much lower ($0.8 mg/g) for carbon AG-5 oxidized with 30% H 2 O 2 and $70 mg/g for adsorbents in studies Zhang et al This marked difference in the values of the adsorption of nitrate ions can be caused by several reasons. Above all, Zhang et al conducted the research under static conditions and with solutions of strongly higher concentrations nitrate ions (400 mg/L), while we conducted the sorption process in the dynamic conditions from the solutions with a concentration below 1 mg/L.…”
Section: Sorption Capacity Of the Adsorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very important to select the appropriate nitrate adsorption material [8,9]. Many materials, such as activated carbon, sepiolite, chitosan and ion exchange resin [8,[10][11][12] can remove nitrate in water, but most of these compounds have high production costs, complex synthesis processes or are difficult to regenerate. Accordingly, they are not suitable for the treatment of large areas of nitrate-contaminated water.…”
Section: Introductionmentioning
confidence: 99%